Bahasa Inggris - Anwar, Rivaldi; Pujiawati, Nia; Mobit, Mobit (Jurnal Ilmiah Wahana Pendidikan, 2024)
Integrating 21st-century skills into textbooks is very important to accommodate students' needs for the 21st-century skills to face the global era. This study investigates the integration of the 21st-century skills in the Merdeka Curriculum English Textbooks for the tenth-grade students. Content analysis was employed as the research design. The researchers used checklist method as the instrument and analyzed the findings by using a descriptive approach. The result of the analysis revealed that 11 of the 21st-century skills were integrated into the textbook, including the essential skills such as critical thinking, problem-solving, effective communication, collaboration, creativity, and innovation. The textbook also includes various other skills, such as media literacy, leadership and responsibility, information and communication technology (ICT), productivity and accountability, initiative and self-direction, social and cross-cultural, and flexibility and adaptability. The 11 skills are included through Nunan’s (2004) task components, namely goals, inputs, procedures, learner roles, and settings. The integration is also completed through other strategies, such as pictures and quotes. In conclusion, this textbook has fulfilled skills which required by current context of education, so that students are capitalized by the appropriate characteristics.